2017
DOI: 10.1134/s1607672917060023
|View full text |Cite
|
Sign up to set email alerts
|

Population status of Greenland halibut Reinhardtius hippoglossoides (Walbaum, 1793) of the Laptev Sea

Abstract: This is the first study to perform a comparative genetic analysis of Greenland halibut in the samples from the Atlantic (waters of west and east of Greenland), Arctic (Laptev Sea), and Pacific (the western part of the Bering Sea) ocean basins using seven microsatellite loci. The obtained data clearly demonstrate that the Greenland halibut population in the Laptev Sea belongs to the groups of the Atlantic Ocean basin. Apparently, the Greenland halibut of the Laptev Sea is represented by a dependent population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…While our model suggests a relatively large geographic distance between the eastern Bering Sea spawning area (Sohn et al, 2010;Duffy-Anderson et al, 2013) and the suitable habitat in the Arctic Ocean, it is still possible that individuals move between these locations as has been shown for the Atlantic side where Greenland halibut migrate from Svalbard to Iceland (Albert and Vollen, 2015). So far, the only studies comparing the Bering Sea population with Atlantic populations using microsatellites indicated that these populations might be genetically separated (Orlova et al, 2017(Orlova et al, , 2019. Further, studies have suggested that Greenland halibut is divided into two populations in the North Atlantic: the Northwest containing Newfoundland, Davis Strait and Baffin Bay, and the Northeast containing Iceland, Norway, and Russia (Knutsen et al, 2007;Westgaard et al, 2017), while another study in the Northwest Atlantic found evidence for panmixia (Roy et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…While our model suggests a relatively large geographic distance between the eastern Bering Sea spawning area (Sohn et al, 2010;Duffy-Anderson et al, 2013) and the suitable habitat in the Arctic Ocean, it is still possible that individuals move between these locations as has been shown for the Atlantic side where Greenland halibut migrate from Svalbard to Iceland (Albert and Vollen, 2015). So far, the only studies comparing the Bering Sea population with Atlantic populations using microsatellites indicated that these populations might be genetically separated (Orlova et al, 2017(Orlova et al, , 2019. Further, studies have suggested that Greenland halibut is divided into two populations in the North Atlantic: the Northwest containing Newfoundland, Davis Strait and Baffin Bay, and the Northeast containing Iceland, Norway, and Russia (Knutsen et al, 2007;Westgaard et al, 2017), while another study in the Northwest Atlantic found evidence for panmixia (Roy et al, 2014).…”
Section: Discussionmentioning
confidence: 67%
“…Greenland halibut (Reinhardtius hippoglossoides; also known as Greenland turbot or black halibut) is a commercially important flatfish supporting demersal fisheries in northern regions of both the Atlantic and Pacific Oceans (Smidt, 1969;Godø and Haug, 1989;Bowering and Brodie, 1995) with some records along the continental slope of the Arctic Ocean (Figure 1; Hedges et al, 2017;Majewski et al, 2017;Orlova et al, 2017;Mecklenburg et al, 2018). Although considered a demersal species, Greenland halibut largely feed on pelagic prey (Hovde et al, 2002;Vollen and Albert, 2008;Dwyer et al, 2010;Giraldo et al, 2018) and individuals may be in the pelagic realm for 10-20% of the time (Albert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Greenland Halibut Reinhardtius hippoglossoides (Walbaum, 1793) is a widespread commercially valuable species, which may be found in large quantities in the northernmost regions of the Atlantic and Pacific oceans as well as in the Arctic seas [ 34 ]. This species is also important groundfish fishery in Atlantic Canada [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of Atlantification on individual fish species and fish communities in the Arctic has not been sufficiently studied. Most of the published information on this problem concerns the European Arctic (mainly the Barents Sea and Greenland waters) or the range extensions into Arctic waters of large boreal fish species capable of distant active migrations, such as Atlantic cod Gadus morhua, haddock Melanogrammus aeglefinus, beaked redfish Sebastes mentella, and Greenland halibut Reinhardtius hippoglossoides [3,12,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%